A trinity technique for prevention of low rectal anastomotic leakage in the robotic era. Issue 10 (October 2020) - Chang, Wenju; Liu, Tianyu; Ren, Li; He, Guodong; Ji, Meiling; Jian, Mi; Chen, Yijiao; Liang, Fei; Wei, Ye; Xu, Jianmin
Abstract: Background: Anastomotic leakage (AL) is a severe complication of low anterior resection (LAR) for rectal cancer, and effective prevention is urgently needed. In the robotic era, this study aimed to explore the role of innovative techniques in preventing AL in rectal cancer patients undergoing robotic LAR. Methods: From May 2012 to May 2017, a total of 601 patients underwent robotic LAR, with 191 patients participated as control subjects (non-PST group) and 410 patients are subjected to a trinity technique (PST group). The AL rate, short-term and long-term outcomes are analyzed and compared. Results: The overall rate of AL was 6.8% out of 601 patients, with Grade B at 5.7% and Grade C at 1.1%, using the ISREC grading system. The PST group presented lower incidence of both overall AL (5.1% vs 10.5%, P = 0.015) and major AL (0.2% vs 3.2%, P = 0.005), when compared with the non-PST group, respectively. Furthermore, the PST group had similar surgical complications (17.3% vs 20.9%, P = 0.286), while with lower re-hospitalization rate (2.7% vs 6.3%, P = 0.038) and reoperation rate (0.2% vs 4.2%, P = 0.001), compared with the non-PST group, respectively. Short-term recovery and long-term oncological outcomes were not significant in the two groups. By multivariate logistic regression models, the risk factors of AL of robotic LAR are confirmed as non-PST technique, estimated blood loss ≥100 mL, anastomosis from anal verge <5 cm, and distal resection margin from tumor <2 cm. Conclusions: The innovative PST technique may shed light on an effective method for preventing occurrence of AL in robotic LAR. Highlights: PST technique is a trinity technique for prevention of AL in the robotic LAR. PST technique contains three core components. PST technique decreases AL with low rate of preventative diverting stoma.